2018
DOI: 10.1016/j.envint.2018.09.048
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic, one carbon metabolism and diabetes-related outcomes in the Strong Heart Family Study

Abstract: Background: Inorganic arsenic exposure and inter-individual differences in its metabolism have been associated with cardiometabolic risk. A more efficient arsenic metabolism profile (lower MMA%, higher DMA%) has been associated with reduced risk for arsenic-related health outcomes; however, this profile has also been associated with increased risk for diabetes-related outcomes. The mechanism behind these contrasting associations is equivocal; we hypothesized one carbon metabolism (OCM) may play a role. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 111 publications
0
20
0
Order By: Relevance
“…In the study by Spratlen et al [30], vitamin B 2 intake was positively related with urinary %DMA, while no such relationship was shown in other studies [27,28,[31][32][33]. In contrast, a negative association with %iAs was shown in the study by Spratlen et al [30], while no such relationship was observed in other studies [27,28,[31][32][33]. There was no significant relationship between vitamin B 2 intake and urinary excretion of tAs [34].…”
Section: Nutrient Intake-ias Metabolismmentioning
confidence: 88%
See 4 more Smart Citations
“…In the study by Spratlen et al [30], vitamin B 2 intake was positively related with urinary %DMA, while no such relationship was shown in other studies [27,28,[31][32][33]. In contrast, a negative association with %iAs was shown in the study by Spratlen et al [30], while no such relationship was observed in other studies [27,28,[31][32][33]. There was no significant relationship between vitamin B 2 intake and urinary excretion of tAs [34].…”
Section: Nutrient Intake-ias Metabolismmentioning
confidence: 88%
“…Both studies showed a negative association with urinary %iAs [24,30], while the study by Argos et al [34] showed a positive association with tAs in the urine. On the other hand, in several studies, there was no relationship between vitamin B 6 intake and urinary %iAs metabolite excretion [27,28,31,33].…”
Section: Nutrient Intake-ias Metabolismmentioning
confidence: 88%
See 3 more Smart Citations